Around the theory of errors - Sheynin, Oscar (Silesian Statistical Review, 2018)
The aims of the theory of errors and its relations with statistics are described. The term true value of a constant and the subjective approach in the error theory and statistics are explained and illustrated and a hint at the emergence of a new theory of errors is provided
Śląski Przegląd Statystyczny = Silesian Statistical Review, 2018, Nr 16, s. 69-76
Keywords: theory of errors and statistics; true value of constant; subjective approach inerror theory and statistics; teoria błędów; statystyka; prawdziwa wartość stała; podejście subiektywne